Edible oil structuring : concepts, methods, and application - Patel, Ashok R. (Royal Society of Chemistry, 2018)
Driven both by real industrial needs and curiosity for fundamental research, edible oil structuring has emerged as a subject of growing interest to students, academics and scientists involved in the research of this field.
Keywords: Oils and fats, Edible.; elektronické knihy; electronic books